HYDROCARBONS IN THE WATER AND BOTTOM SEDIMENTS OF A REGION WITH CONTINUOUS PETROLEUM CONTAMINATION - Nemirovskaya I.A. (My University, 2007)
The abundances and compositions of aliphatic hydrocarbons (AHC) and polyaromatic hydrocarbons (PAH) were investigated in the water and bottom sediments of the southwestern Amur Bay in the Sea of Japan. The water contained from 0 to 129 μg/1AHC (averaging 42.2 μg/l) and from 5 to 85 ng/l PAH (averaging 18 ng/l). The bottom sediments contained 168-2098 μg/g AHC and 7.2-1100 ng/g dry mass PAH. It was shown that the input of anthropogenic HC is better recorded by molecular markers than the distribution of AHC and PAH concentrations. The discovery of elevated HC concentrations in the bottom water layer suggests that the bottom sediments induced secondary contamination of the water body. © Pleiades Publishing, Ltd. 2007.